(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the effectiveness of management practices towards customer satisfaction at Kaori John Grocery Store. It aims to improve and enhance the knowledge about reaching the business’s success and how effective the management is. This study used the Contingency Management Theory and the Expectancy-Disconfirmation Paradigm. Both theories mentioned are relevant as they imply the concept of scientific management, which is related to the variable cited in this. Management implies customer satisfaction and organization of business. The study utilized a descriptive research method and convenience sampling where the researchers focused on fifty (50) customers of Kaori John Grocery Store and created four (4) parts of the survey questionnaire based on the problem of the studies. The researcher uses frequency and percentage to determine the respondents and the description according to age, gender, and maximum spent on the purchase and uses weighted means to define the level of performance in terms of service quality, security, working condition, place, price, product, customer behaviour, staff performance, and transaction. From the findings and conclusion, Kaori John Grocery Store was evaluated as "satisfied" and "strongly agree" by the respondents. Kaori John Grocery Store should be productive in assessing customers and must implement new strategies to expand the business. Furthermore, based on the recommendation, Kaori should enhance the quality of services they give to their customers. They must keep setting goals for the improvement of their level of management that are connected to the performance that leads to customer satisfaction. Look up to their business internally and externally and provide a training program for their employees. This study shows the importance of how management can help to develop a business towards success.